A Web-Based Library Management System with Notifications and AI-Powered Search at SMAN 1 Tambang - Ilvi Maulidya Nurulisa; Asrul Huda; Dedy Irfan; Vera Irma Delianti (Universitas Negeri Padang, 2026)
Secondary school libraries in Indonesia largely remain dependent on manual or semi-digital record-keeping even as digital library adoption grows at the university level, creating gaps in data accuracy, user access, and accreditation readiness. This study addresses that gap by designing and developing a web-based library management system for SMAN 1 Tambang that integrates five functionalities which, based on the literature reviewed in this study, have not previously been reported within a single school library management system: AI-powered natural-language search using the Gemini API, automated WhatsApp overdue notifications via the Fonnte API, six-role access control, digital rights management (DRM) for digital collections, and QRIS-based fine payment through Midtrans. The system was developed using the Waterfall method, Laravel 12, MySQL, and Bootstrap 5. Black Box Testing across 30 scenarios achieved a 100% success rate. The AI search feature achieved an overall Precision of 69.23%, Recall of 75.00%, and F1-Score of 71.96%, with an average response time of 866 ms, while Load Testing recorded a 0.00% error rate under loads of 10–100 concurrent users. User Acceptance Testing involving 30 respondents yielded a mean score of 4.30 out of 5.00 (